Association between Ki67 After Neoadjuvant Chemotherapy and Disease-Free Survival in Breast Cancer - Aan Setiawan; Mulawan Umar; Erial Bahar (Surgery Department, Faculty of Medicine Universitas Sriwijaya, 2021)
Background: Post Chemotherapy Ki67 in recent year has been investigated as a predictive and prognostic factor in locally advanced breast cancer patient undergoing neoadjuvant chemotherapy. Objectives: To describe the relationship between post-chemotherapy Ki67 and disease-free survival after neoadjuvant chemotherapy in patients with locally advanced breast cancer at Dr. Hospital. Mohammad Hoesin Palembang. Methods: This study is an analytical observational study with prognostic test design conducted in 30 stage III B breast cancer patient. A retrospective search of a prospectively maintained clinical database was performed to identify patient treated with neoadjuvant chemotherapy at the Mohammad Hoesin Hospital. The expression of Ki67 was assessed using immunohisto-chemistry in post therapy surgical excision specimen. Results: From 30 patients, there was a significant relationship between Post Chemotherapy Ki67 and disease- free survival in patients with locally advanced breast cancer (r = -0,742, p = 0.000). The cut off point value of Ki67 was 27,5% with an area under curve (AUC) of 0,716. The results of the post-chemotherapy Ki67 prognosis test included sensitivity 64%, specificity 60%, Positive Predictive Value 88,9%, Negative Predictive Value 25%, accuracy 63,3%. Conclusion: There is a significant relationship between Post Chemotherapy Ki67 to disease free survival and Post Chemotherapy Ki67 can be used as a prognostic biomarker in breast carcinoma patients undergoing neoadjuvant chemotherapy.